(untitled) (Kinesiology, 2017)
The aim of our research was to describe the joint angular velocities of young basketball players (U16) during their performance of jump shots and to find out what was the effect of increasing shooting range on these velocities. Our sample included 14 players that performed the function of guards. Their average age (±SD) was 15.43±0.51 years. The analysis contemplated 370 field goals, which were performed from three different distances (3.75 m, 5.25 m and 6.75 m) perpendicular to the hoop board. The measurements were performed using an Xsens MVN inertial suit. The results showed that the maximum angular velocity in the shoulder and elbow joint became greater with the increase of shooting range. In the throw from the shortest distance, the segments were integrated into the movement of the shooting arm according to the proximaldistal principle. The temporal sequences of maxima velocities in legs were preserved in throws from all the three distances. The findings are important for young basketball players and their coaches. They have to be aware of the needed adjustments to the techniques of throws from various ranges and they must take them into account when practicing. Key words: jump shot, cadets, guards, proximal-distal principle